Evidence for B- → D[ast][ast]0τ-(𝜈)barτ decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Physical review letters, 2025)
The first evidence for the decay 𝐵−→𝐷**0⁢𝜏−⁢‾𝜈𝜏 is obtained using proton-proton collision data collected by the LHCb experiment, corresponding to an integrated luminosity of 9 fb−1, at centre-of-mass energies of 7, 8, and 13 TeV. Here, the 𝐷**0 meson represents any of the three excited charm mesons 𝐷1⁢(2420)0, 𝐷*2⁢(2460)0, and 𝐷′1⁢(2400)0. The 𝐵− →𝐷**0⁢𝜏−⁢¯𝜈𝜏 signal is measured with a significance of 3.5⁢𝜎, including systematic uncertainties. The combined branching fraction ℬ⁡(𝐵−→𝐷**01,2⁢𝜏−⁢¯𝜈𝜏)×ℬ⁡(𝐷**01,2→𝐷*+⁢𝜋−), where 𝐷**01,2 denotes both 𝐷1⁢(2420)0 and 𝐷*2⁢(2460)0 contributions, is measured to be [0.051±0.013⁢(stat)±0.006⁢(syst)±0.009⁢(ext)]%, where the last uncertainty reflects that of the branching fraction of the normalization channel 𝐵− →𝐷**01,2⁢𝐷−𝑠(*). The ratio between the tauonic and muonic semileptonic 𝐵 decays, with the latter taken from world average values, is also determined and found to be ℛ⁡(𝐷**01,2)=0.13±0.03⁢(stat)±0.01⁢(syst)±0.02⁢(ext).